A study on effective sterilization of vaginal cone used for pelvic floor dysfunction patients. - G.DEEPTHI; MANIPRIYA; DR.PRATHAP SUGANTHIRABABU; DR.HEPZIBAH KIRUBAIMANI; P.SANKARA KUMARAN; J. LAVANYA PRATHAP; HEMA SWAROOPA (International Journal of Pharma and Bio Sciences, 2017)
The vaginal cone is a medically designed device used as resistance for pelvic floor training. Resistance training is nothing but making the muscles to contract against an external resistance. It increases muscle strength, tone, mass, and/or endurance. Since this device is administered in genital tract it requires effective sterilization as it has high chances for spreading infections when the same cone is used for many patients in hospital set up and there are chances for recurrence of the infections in individuals if persists when it is used single handed. So the effective sterilization is mandatory. The present study was conducted to determine the effect of detergent washing, boiling water, surgical spirit and autoclave in sterilizing the vaginal cone which is used for the patients with pelvic floor dysfunction. Using simple random sampling method based on inclusion and exclusion criteria twenty patients were selected from Department of Obstetrics and Gynecology, Saveetha Medical College and Hospital, Chennai. The patient was given pelvic floor exercise with vaginal cone for fifteen minutes twice a day under the supervision of physiotherapists and the vaginal cone was taken out of the vagina and was washed in the running water with normal bathing soap, air dried and sample was taken with sterile cotton swab by swabbing it over the cone. Then the same procedure was repeated by putting the vaginal cone in boiling water for 5 minutes, surgical spirit and autoclave in consecutive sessions. The sample was given for culture using three different medias. Three out of the twenty samples which was collected after detergent washing showed growth and rest of the samples were inactive. Streptococcus pyogen were the predominant isolated bacteria found. The 20 samples done with boiling water, ethanol and autoclave did not show any growth at all. This study concludes that the boiling water, ethanol and autoclave can be used for vaginal cone sterilization. The detergent washing can also be used with precautions and combined with other methods for domiciliary sterilization and it needs further more research with large sample size.